2009
DOI: 10.1073/pnas.0908262106
|View full text |Cite
|
Sign up to set email alerts
|

A little bit of lithium does a lot for hydrogen

Abstract: From detailed assessments of electronic structure, we find that a combination of significantly quantal elements, six of seven atoms being hydrogen, becomes a stable metal at a pressure approximately 1/4 of that required to metalize pure hydrogen itself. The system, LiH6 (and other LiHn), may well have extensions beyond the constituent lithium. These hypothetical materials demonstrate that nontraditional stoichiometries can considerably expand the view of chemical combination under moderate pressure.high pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
250
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 265 publications
(263 citation statements)
references
References 32 publications
10
250
3
Order By: Relevance
“…The situation thus differs markedly from LiH n , 2 and also from CaH n 5 where for certain stoichiometries one clearly finds paired hydrogens. There is a definite connection to the CaH 6 structure at 150 GPa, 5 which features an extended H network, albeit different from the ones we find here.…”
Section: N the Hydrogen Sublatticementioning
confidence: 89%
See 1 more Smart Citation
“…The situation thus differs markedly from LiH n , 2 and also from CaH n 5 where for certain stoichiometries one clearly finds paired hydrogens. There is a definite connection to the CaH 6 structure at 150 GPa, 5 which features an extended H network, albeit different from the ones we find here.…”
Section: N the Hydrogen Sublatticementioning
confidence: 89%
“…In equation (2), N f is the electronic density of electron states at the Fermi level. The linewidth γ q j of a phonon mode j at wave vector q, arising from EPC is given by…”
Section: Computational Detailsmentioning
confidence: 99%
“…We propose to call these chemically active H 2 units perhydride groups; they have so far not been observed at ambient conditions, but predicted to exist at high pressures in GeH 4 (ref. 17) and unique lithium hydrides LiH 2 , LiH 6 and LiH 8 (39). Perhydride groups were also predicted in the structures of SnH 4 calculated in refs.…”
Section: 63)mentioning
confidence: 99%
“…Introduction of an electronegative element, as was demonstrated in the case of K-Ag (16), increases the ability of the electronegative Ag atoms to accommodate electrons from K into the outermost 5s and 5p valence shells, thereby forming a bonding network and stabilizing the alloy structures that otherwise would not be observed under ambient pressures. Recently, Zurek et al (17,18) demonstrated that charge transfer from lithium or sodium to hydrogen molecules under high pressures could lead to the formation of new metallic lithium-or sodium-hydride alloys. Depending on the stoichiometry, the structures consist of "predissociated" molecular H 2 and/or monoatomic hydrogen.…”
mentioning
confidence: 99%